Identification of barriers and facilitators of successful interprofessional education (IPE) - a scoping umbrella review / Identifizierung der Einflussfaktoren für die interprofessionelle Ausbildung (IPE) - ein Umbrella Scoping Review - Handgraaf Marietta; Wallin Jasmin; Groll Christina; Posenau André (Sciendo, 2023)
The study aims to provide an overview of factors influencing interprofessional education (IPE).